SHARIA ECONOMIC HARMONY: RECONSTRUCTING PEACE THROUGH NEGOTIATION AND MEDIATION IN CONFLICT RESOLUTION - Badruddin Badruddin; Muhammad Syam'ani; Mariani Mariani (SEAN Institute, 2023)
This article aims to reconstruct peace through negotiation and mediation in resolving Sharia economic conflicts. The focus is on negotiation and mediation, which are among the alternative dispute resolution methods in Sharia economics today. To approach this issue, references to mediation theory, Sharia economic law, dispute resolution, and peace are utilized. Data is collected through public or perish with the goal of searching Google Scholar for scholarly works such as books, journals, and other secondary materials, and analyzed qualitatively. This study concludes that resolving Sharia economic conflicts through negotiation or mediation is a crucial approach to achieving peace and justice. The article details the fundamental concepts of negotiation and mediation and their reconstruction in resolving Sharia economic conflicts. Legal sources regulating negotiation and mediation in Indonesia are also explained. Some challenges in negotiation and mediation, such as knowledge and time limitations, and ways to overcome them, are discussed. Peace reconstruction requires competent negotiators and mediators, proper procedures to build trust, the use of suitable techniques, and consideration of alternative dispute resolution. By understanding these concepts, the resolution of Sharia economic conflicts can become more effective and beneficial for all parties involved.